PENDIDIKAN KARAKTER SISWA SD NEGERI BUARAN ASEM DESA TANJUNG ANOM DI ERA DIGITAL - Aisyah Amalia; Siti Fatimatuz Zahrah; Muhammad Fauzan Muttaqin (Education and Community Service Journal (EduServe), 2025)
The phenomenon of easy access to information in the digital age has a significant impact on the development of elementary school children. On one hand, technology makes it easier for children to acquire knowledge quickly, but on the other hand, it also has negative effects, such as a tendency to imitate bad behavior, a decline in discipline, and a weakening of healthy social interactions. This situation poses a serious challenge for the education sector, especially in instilling character values from an early age. This community service article aims to strengthen character education for elementary school students as a moral fortress in facing the onslaught of digital trends. The activities were held at Buaran Asem State Elementary School, Tanjung Anom Village, Tangerang Regency, involving teachers, students, and school communities through various habituation activities, mentoring, and interactive methods based on active participation. The implementation method uses a participatory approach, where students are involved in educational activities such as value games, simple discussions, role simulations, and daily reflections. The teacher acts as a role model to guide students in applying the values of honesty, responsibility, care, and discipline in everyday life. The research results show that these activities can cultivate students' awareness to behave more orderly, appreciate friends, and enhance social care in the school environment. The implications of these findings indicate that character education is not only relevant but also urgent to continue developing as an integral part of the elementary school curriculum. Strengthening character from an early age has proven to be an effective strategy to anticipate moral degradation due to the negative impacts of the digital era while equipping young generations with a strong moral foundation for the future.